Assessment of Probable Drug-Drug Interactions in IPD Geriatric Patients at Tertiary Care Teaching Hospital - Purantar, Akshata Manjunath; Nyamagoud, Sanatkumar Bharamu; Swamy, Agadi Hiremath Viswanatha; Jangliwale, Bibi Khuteja; Kumar, Kaushal; T P, Rakshita (International Journal of Pharmaceutical Investigation, 2025)
Background Older adults are at a higher risk of experiencing drug-drug interactions due to their tendency to use several medications simultaneously, which may include prescription medications, over-the-counter products and dietary supplements. The presence of polypharmacy among older adults complicates treatment, raises healthcare costs and poses challenges for healthcare organizations. This systematic review explores how pharmacist-led interventions can effectively address and reduce polypharmacy, considering the changing responsibilities of pharmacists in patient care. Materials and Methods The research was a prospective observational study conducted over a period of six months, focusing on inpatients at Vivekananda General Hospital. Micromedex was employed to evaluate drug-drug interactions. Results In this research, 200 elderly people were examined, in which 109 were males and 91 were females. The participants in the study were 69.5 (±5.0) years old on average. In the general population, 191 (95.5%) Comorbidities among the individuals were reported. The most prevalent chronic diseases were hypertension (53.4%), Next in line is type 2 diabetes (31.3%) and hypothyroidism was the least common condition (1.6%). The subjects were analysed for DDI’S using Micromedex, among which 132 (66%) patients were observed with 154 Drug-Drug Interactions. Majority were found in female 82 (62.12%) followed by 50 (37.87%) males. Based on severity, the discovered DDIs were divided into three categories: severe, moderate and small. Among 154 drug-drug interactions identified, 89 (57.79%) were discovered to be major, 36 (23.37%) were identified to be moderate and 7 (4.54%) were determined to be minors. Conclusion Our research underscores the significance of managing drug-drug interactions in elderly patients. It is crucial to provide targeted care to this population to prevent these interactions, particularly given the prevalence of comorbidities, polypharmacy and low health literacy.
Keywords: Drug-Drug interactions; Geriatrics; Polypharmacy